Border Insecurity and the Challenges of Transnational Terrorism in North East Nigeria - Hamidu, Ishaku (International Journal Labs, 2022)
Background: Using secondary sources of data, and adopting transnationalism theory, it is discovered that Nigeria’s territory and population are vulnerable. Consequently, the border towns and its people become prey to transnational terrorists’ organizations; drug barons; smugglers; among others. Some frontline settlers are conscripted into or give support to the criminal elements; engage in illegal smuggling, thereby making the state lose vital revenue from some traders and corrupt state officials at the border posts. Aim: The study looked at some of the literature on border security and insecurity, terrorism on both a domestic and international scale, the effects of porous border security on people's lives, property, and socioeconomic activities, and the implications for those living in the border region of northeastern Nigeria. Method: Articles from magazines, newspapers, textbooks, and other resources were compiled. The many authors' viewpoints and contents are studied or addressed in the sections that follow. Findings: Border insecurity is the factor responsible for the inability of the states to halt the terrorists’ activities across Nigerian international boundary in the north-east axis. Government is therefore urged to establish its authority in those frontline states; equip the nation’s security operatives; boost cross-border security surveillances; provide social infrastructures for those at the border to make them patriotic and loyal to the state as the panacea for halting trans-border criminality and terrorism in the North-East in particular and Nigeria at large.